Socio‐economic impact of solar cooking technologies on community kitchens under different climate conditions: A review - Ashutosh Verma (36178) (2024)
Residential cooking with non‐renewable energy sources, such as firewood, charcoal, natural gas, participate in the emission of more than a gigaton of CO2 per year, which represents 2% of the global CO2 emissions. Additionally, toxic particles including sulfur dioxide, carbon monoxide, and mercury are released leading to elevated levels of indoor air pollution, and adversely affecting the health of the inhabitants. The residential sector's non‐renewable energy cooking devices also pose significant problems, consuming approximately 30%–40% of global energy usage, with over 80% dedicated to cooking applications. To mitigate the negative impacts of traditional cooking on health and the environment, various renewable energy‐based cooking technologies have been developed recently. The primary contributions of our paper are to: (a) present a comprehensive review of concentrated solar thermal cooking technologies, assessing their social, economic, and environmental impact across different climatic zones in developing countries like India; (b) classify and compare different solar cooking technologies, highlighting their advantages and limitations in various scenarios; (c) evaluate the energy efficiency of diverse solar cooking technologies; (d) analyze the impact of solar cookers on communities in developing countries; and (e) identify the challenges and future directions for solar cooker technologies, particularly in solar community kitchens. Our novel findings demonstrate that using solar cooking devices can reduce energy consumption by up to 56% in Indian schools. Moreover, the payback period ranges from 3 to 6 years, contingent on the technology's cost, climatic conditions, and available subsidies. Consequently, significant positive impacts on society, the economy, and the environment are observed when traditional cooking devices are replaced by solar cooking devices. This study provides a unique and thorough analysis, contributing to the growing body of knowledge on sustainable cooking solutions and their potential to transform energy consumption patterns in developing regions. Other Information Published in: Engineering Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/eng2.12998